The use of endoscopic photodynamic therapy in combined treatment of gastric cancer (review of literature) - A. A. Zakharenko; A. H. Khamid; A. A. Svechkova; M. A. Belyaev; K. N. Vovin; A. V. Prudnikov (Вестник хирургии имени И.И. Грекова)
With the successes achieved in the treatment of gastric cancer, the problem of combined neoadjuvant therapy for stenosing tumors remains unresolved. To find the optimal method of treatment, we carried out the analysis of modern domestic and foreign literature. The standard methods are the implantation of a self- expandable stent, argon-plasma coagulation, the implantation of a nasointestinal feeding tube, the formation of gastroenteroanastomoses, gastro/enterostomy. However, there is no evidence base about the effectiveness and safety of the above methods when applying them as part of the combined treatment of potentially operable gastric cancer. The method of endoscopic photodynamic therapy seems promising.